(untitled) (Bangladesh Journal of Zoology, 2024)
Morphometric features are efficiently used for the differentiation of species and long-term management of fish populations. Truss analysis is a frequently used taxonomic method as well as a stock identification tool to dissimilitude the morphologically similar species. Using landmark-based truss networking techniques following 18 morphometric lengths, 10 meristic counts, and 23 truss-network distance, the morphological variation of three croaker species viz. Johnius borneensis, Johnius argentatus, and Johnius belangerii were examined from Bangladesh coast. Data were analyzed and visualized through univariate ANOVA, canonical discriminate function analysis (DFA), and principal component analysis (PCA). Results found that the first DFA was responsible for 80.6% & 81.1%, whereas the second DFA was responsible for 19.4% & 18.9% variations among three species for the morphometric and truss-distances, respectively. In addition, 14 out of 18 morphometric and 12 out of 23 truss-network measurements were significantly different (p < 0.05) among means of three species. 1st PCA found 70.76% & 64.49% explained variations and 2nd PCA displayed 12.8% & 11.5% explained variations respectively for morphometric and truss distances. The findings of the study demonstrates that J. borneensis and J. belangerii are highly morphologically similar and J. argentatus is completely distinct which might be due to their physiological and genetic variations. The present study might be helpful in differentiating species and managing existing stocks of marine fish. Further studies regarding the molecular characterization of the Cytochrome c oxidase subunit I (COI) gene could confirm the genetic variations among these species. Bangladesh J. Zool. 51(3): 233-251, 2023